KORELASI ANTARA RASIO NEUTROFIL LIMFOSIT DENGAN VOLUME INFARK SEREBRI PADA PENDERITA STROKE ISKEMIK AKUT - Ilsa Hunaifi; Triana Dyah Cahyawati (NEURONA, 2019)
CORRELATION BETWEEN NEUTROFIL LIMPHOCYTE RATIO AND CEREBRAL INFARCTION VOLUME IN ACUTE ISCHAEMIC STROKEABSTRACTIntroduction: Inflammation plays a key role in stroke pathophysiology. Neutrophils is one of the earliest leucocyte subtypes to infiltrate the ischemia area of the brain. The neutrophil-lymphocyte ratio (NLR) is independent of the severity of coronary heart disease and as a predictor of poor clinical outcomes in patients with coronary heart disease undergoing angiography. The neutrophil-lymphocyte ratio values may be a prognostic factor in ischemic stroke patients. The neutrophil- lymphocyte ratio values can also be used in predicting infarct size, however limited study has been conducted in this area.Aim: To determine the correlation of NLR with cerebral infarct volume in acute ischemic stroke patients.Method: This was an analytical observational study with cross sectional design. The population for this study were acute ischemic stroke patients at NTB Genereal Hospital. The collected data were analyzed by Spearman correlation test.Results: Approximately 52 participants  were enrolled in this study with mean age was 59.79±8.65 years old. Hypertension was a common modifiable risk factor identified in more than 94.2 % participant. The mean of neutrophil lymphocyte ratio was 3.94±2.96 and mean of infarct volume was 13.96±37.26cm3. There was correlation between RNL and cerebral infract volume (r=+0.351; p=0.023).Discussions: Higher lymphocyte neutrophil ratio in acute ischemic stroke patients would result in an increase of brain infarct volume.Keyword: Infarct volume, ischaemic stroke, neutrophil lymphocyte ratioABSTRAKPendahuluan: Inflamasi memegang peranan penting dalam patofisiologi stroke. Salah satu subtipe dari sel leukosit yang paling awal menginfiltrasi ke area iskemia di otak adalah neutrofil. Rasio neutrofil limfosit (RNL) merupakan faktor independen terhadap beratnya penyakit jantung koroner dan sebagai prediktor luaran klinis yang buruk pada penderita penyakit jantung koroner yang menjalani angiografi. Nilai RNL dapat menjadi faktor prognostik pada penderita stroke iskemik. Nilai RNL juga bisa digunakan dalam memprediksi ukuran infark namun belum dilakukan penelitian hingga saat ini.Tujuan: Mengetahui korelasi RNL dengan volume infark serebri pada penderita stroke iskemik akut.Metode: Penelitian analitik observasional dengan desain potong lintang terhadap pasien stroke iskemik akut di RSUP NTB. Data yang terkumpul dianalisis dengan uji korelasi Spearman.Hasil: Didapatkan 52 subjek dengan rerata umur 59,79±8,65 tahun dan faktor risiko utama hipertensi (94,2%). Didapatkan rerata rasio neutrofil limfosit 3,94±2,96 dan rerata volume infark 13,96±37,26cm3. Terdapat korelasi antara RNL dengan volume infark serebri (r=+0,351; p=0,023).Diskusi: Semakin tinggi nilai rasio neutrofil limfosit mengakibatkan semakin luasnya volume infark serebri pada penderita stroke iskemik akut.Kata kunci: Rasio neutrofil limfosit, stroke iskemik, volume infark